Investigation of the importance of heat transfer during thin electrolyte formation in atmospheric corrosion using a novel experimental approach. (15th August 2021) - Koushik, B.G.; Van den Steen, N.; Terryn, H.; Van Ingelgem, Y.
Graphical abstract: Highlights: Novel approach to investigate the behavior of thin-film electrolyte on metal surface. Experimental validation of a pre-existing dynamic electrolyte film model (DEFM). Importance of natural heat transfer coefficient during atmospheric corrosion process. Abstract: During atmospheric corrosion of metals, the evolution of thin-film electrolyte thickness is the primary factor that determines corrosion rate. Understanding the evolution of the electrolyte thickness as a function of the key environmental parameters is yet to be achieved. Therefore, in the present article, a novel methodology has been developed to conduct experiments under regulated environment to measure the evolution of the film thickness on an undisturbed metal surface using an interferometer. Experimental results are compared with the previously developed simulation model. The heat transfer coefficient is noted as a critical parameter influencing the film characteristics and resulting corrosion rate.